Factor Associated to the Decision-Making Behavior for Receiving the COVID-19 Booster Vaccination among Patients Visiting in Medical Department of a Tertiary Hospital in Pathum Thani Province - ตันธนปัญญากร ปัณณทัต; ขันติกุลานนท์ นลพรรณ; จันทร์มาลี ศศิวิมล; จำเนียรสุข อภิเชษฐ์ (Journal of Health Science of Thailand, 2023)
The research was a cross-sectional analytical study aimed to investigate the factors associated with the decision-making behavior for receiving the COVID-19 booster vaccination among patients visiting the medical department of a tertiary hospital in Pathum Thani province. The participants consisted of 385 patients who had chronic diseases and were aged 15 years and older. They were recruited by purposive random sampling based on the inclusion criteria. Data were collected by self-administration between November to December 2022. The measurement tool was the questionnaire, which consisted of seven parts including a personal data questionnaire, knowledge assessment form, attitude assessment form, and decision-making behavior assessment form about COVID-19 booster vaccination. Data were analyzed by using descriptive statistics and multiple logistic regression analysis. The results showed that the majority of the samples had high level of decision-making behavior for receiving the covid-19 booster vaccination (56.3%), followed by moderate and low level (28.1% and 15.6%, respectively). Factors which remained significantly associated with decision-making behavior for receiving the COVID-19 booster vaccination were educational level (ORAdj=2.60, 95% CI=1.46-4.63, p=0.001), health insurance (ORAdj=9.00, 95% CI=3.07-26.41, p<0.001), knowledge of the COVID-19 vaccination (ORAdj=5.44, 95% CI=2.99-10.20 p<0.001), and attitudes towards with vaccination against COVID-19 (ORAdj=12.00, 95% CI=5.28-27.30, p<0.001). Findings suggest that the healthcare provider can apply the data for prevention and lay down measures to promote the right knowledge and appropriate attitudes towards the COVID-19 booster vaccination, which led to prevent of infection and reduce the potential severity